What were they thinking? : unconventional wisdom about management - Pfeffer, Jeffrey (Boston, Mass. : Harvard Business School Press, 2007)
Every day companies and their leaders fail to capitalize on opportunities because they misunderstand the real sources of business success. Based on his popular column in "Business 2.0", Jeffrey Pfeffer delivers wise and timely business commentary that challenges conventional wisdom while providing data and insights to help companies make smarter decisions. The book contains a series of short chapters filled with examples, data, and insights that challenge questionable assumptions and much conventional management wisdom. Each chapter also provides guidelines about how to think more deeply and intelligently about critical management issues. Covering topics ranging form managing people to leadership to measurement and strategy, it's good organizational advice, delivered by Dr. Pfeffer himself.
People-centered strategies -- Creating effective workplaces -- Power play: rethinking leadership and influence -- Measures of success: rethinking organizational strategy -- Facing the nation: organizations and public policy.
Includes bibliographical references (pages [195]-211) and index.
Description based on print version record.
Keywords: Management; Supervision of employees; Leadership; Organizational behavior; Leadership; Management; Organizational behavior; Supervision of employees; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books